What do Unions Do? Media Framing of the Two‐Faces of Labor. Issue 4 (30th November 2016) - Brimeyer, Ted; Silva, Eric O.; Byrne, R. Jolene
Abstract : In What Do Unions Do? Freeman and Medoff argued that researchers need to focus on both the collective voice face (positive) and monopoly face (negative) of unions in their analyses of organized labor. While economists have used this typology in their research, other fields have generally ignored it. This research explores media coverage of organized labor using an original coding scheme based on the work of Freeman and Medoff. The New York Times', Washington Post's, and Wall Street Journal's coverage of the Employee Free Choice Act were analyzed to determine if the two‐face typology is evident in media coverage of unions, if the articles could be coded reliability using the scheme, and how the results compared to previous content analyses of labor. Results show that the scheme can be used reliably and that, similar to other studies, unions are portrayed negatively. We conclude with suggestions for further research using the two‐face typology in the analysis of organized labor.